The coagulation system and its function in early immune defense - Poll, Tom van der; Herwald, Heiko (Thrombosis and Haemostasis, 2014)
Blood coagulation has a Janus-faced role in infectious diseases. When systemically activated, it can cause serious complications associated with high morbidity and mortality. However, coagulation is also part of the innate immune system and its local activation has been found to play an important role in the early host response to infection. Though the latter aspect has been less investigated, phylogenetic studies have shown that many factors involved in coagulation have ancestral origins which are often combined with anti-microbial features. This review gives a general overview about the most recent advances in this area of research also referred to as immunothrombosis.
Keywords: Bacterial infection; coagulation factors; disseminated intravascular coagulation (DIC); immunity; infectious diseases